2009
DOI: 10.1007/978-3-642-00457-5_31
|View full text |Cite
|
Sign up to set email alerts
|

Goldreich’s One-Way Function Candidate and Myopic Backtracking Algorithms

Abstract: Abstract. Goldreich (ECCC 2000) proposed a candidate one-way function construction which is parameterized by the choice of a small predicate (over d = O(1) variables) and of a bipartite expanding graph of right-degree d. The function is computed by labeling the n vertices on the left with the bits of the input, labeling each of the n vertices on the right with the value of the predicate applied to the neighbors, and outputting the n-bit string of labels of the vertices on the right.Inverting Goldreich's one-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
31
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 16 publications
(19 reference statements)
2
31
0
Order By: Relevance
“…The strongest known lower bounds were proved using the methods introduced by Ben-Sasson and Wigderson in [BSW01]. From practical point of view it is more interesting to have lower bound for backtracking algorithms on satisfiable formulas; there are several lower bounds on satisfiable formulas [AHI05], [CEMT09], [Its10], [IS12] under various restrictions on heuristics that choose a variable for splitting and a value that would be investigated at first. However all known lower bounds on satisfiable formulas are proved by reduction to lower bounds on unsatisfiable ones.…”
Section: Introductionmentioning
confidence: 99%
“…The strongest known lower bounds were proved using the methods introduced by Ben-Sasson and Wigderson in [BSW01]. From practical point of view it is more interesting to have lower bound for backtracking algorithms on satisfiable formulas; there are several lower bounds on satisfiable formulas [AHI05], [CEMT09], [Its10], [IS12] under various restrictions on heuristics that choose a variable for splitting and a value that would be investigated at first. However all known lower bounds on satisfiable formulas are proved by reduction to lower bounds on unsatisfiable ones.…”
Section: Introductionmentioning
confidence: 99%
“…This work continues [AHI05,CEMT09,Its10] and is devoted to lower bounds of DPLL algorithms on satisfiable formulas. The behaivior of DPLL algorithms on unsatisfiable formulas is equivalent to tree-like resolution proofs.…”
Section: Introductionmentioning
confidence: 93%
“…The paper [CEMT09] gives a cryptographic view on [AHI05]. Namely it was noted in [CEMT09] that the lower bound for myopic algorithms [AHI05] was proved on the formulas that code the problem of inversion of Goldreich's function based on linear predicate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cook et al (2009) showed that a restricted class of algorithms called "myopic algorithms" take exponential time to invert Goldreich's construction. The kinds of algorithms used in this work are not myopic.…”
Section: Introductionmentioning
confidence: 99%